1997
DOI: 10.2134/jeq1997.00472425002600060026x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium in Australian Potato Tubers and Soils

Abstract: Cadmium (Cd) has been identified as a potential contaminant in foods posing health risks to humans and, in Australia, potatoes (Solanum tuberosum L.) have been identified as contributing a large proportion of the average dietary Cd intake. To assess the concentrations of Cd in Australian potatoes and soil factors likely to lead to high Cd concentrations, commercial crops and soils were sampled at 352 sites throughout potato production areas in Australia. Across all states, fresh weight (FW) tuber Cd concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 0 publications
6
37
3
Order By: Relevance
“…In our study, however, Cd concentration in potato tubers was not correlated with soil DTPA-extractable Cd (R 2 00.003, P 0.05) (Fig. 3) or Mehlich 3-extractable Cd (R 2 00.14, P 0.05) (data not shown), in agreement with results from field experiments conducted in Australia (McLaughlin et al 1997). Mehlich 3-extractable Cd was significantly (P B0.005) correlated with DTPA-extractable Cd in soils (Fig.…”
Section: Tuber CD Concentration and Some Selected Soil Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, however, Cd concentration in potato tubers was not correlated with soil DTPA-extractable Cd (R 2 00.003, P 0.05) (Fig. 3) or Mehlich 3-extractable Cd (R 2 00.14, P 0.05) (data not shown), in agreement with results from field experiments conducted in Australia (McLaughlin et al 1997). Mehlich 3-extractable Cd was significantly (P B0.005) correlated with DTPA-extractable Cd in soils (Fig.…”
Section: Tuber CD Concentration and Some Selected Soil Characteristicssupporting
confidence: 90%
“…While many studies on Cd accumulation in potato tubers and the effects of P fertilization on Cd uptake by potato have been conducted in Australia (McLaughlin et al 1997;Dunbar et al 2003), the United States of America (Mulla et al 1980;Wolnik et al 1983;Gartrell et al 1986), and Bolivia (Oporto et al 2007), there are no reports on potato Cd concentration in Canada.…”
mentioning
confidence: 99%
“…The results also suggest that if PR and PAPR are as agronomically effective as fully acidulated P sources, the former may contribute less to Cd uptake by crops than WSP sources. McLaughlin et al (1997) reported that increased chloride (Cl) content in irrigated waters imposes a high risk of producing crops with high Cd concentrations. It is believed that Cl ions form relatively strong complexes with Cd 2?…”
Section: Cadmium In Soils and Plants From Application Of Various P Fementioning
confidence: 99%
“…1998). In Australia, McLaughlin et al (1997) found that fresh weight tuber Cd concentrations ranged from 0.004 to 0.232 mg kg-', with a median of 0.033 mg kg-'. About 25.6% of the samples in their study exceeded the current ma yirman permitted concentration of 0.05 mg kg-'.…”
Section: Future Opportunitiesmentioning
confidence: 99%